MARIE SEONG-HAK KIM, Law and Custom in Korea – Comparative Legal History - Förster, Christian (Zeitschrift für Japanisches Recht, 2015)
MARIE SEONG-HAK KIM Law and Custom in Korea – Comparative Legal HistoryCambridge University Press 2014; XIV, 349 S., 30 €, ISBN 978-1-107-66033-5